PENERAPAN SEKOLAH AKSARA MELALUI METODE CALISTUNG KEARIFAN LOKAL SEBAGAI UPAYA PENGENTASAN TRIBUTA DI DESA TODDOPULIA KECAMATAN TANRALILI KABUPATEN MAROS - Nasiruddin, Fathimah Az Zahra; Basri, Syamsurijal (Jurnal Ilmiah Ecosystem, 2020)
Application of Script Schools through the Calistung Method of Local Wisdom as an Effort to Eradicate Tri blind in Toddopulia Village, Tanralil District, Maros Regency, Fathimah Az.zahra Nasiruddin, Bosowa University. This study aims to 1) find out the Tributa problems experienced by women in Toddopulia village including illiteracy, Indonesian language blindness and basic education blindness. 2) Implement Calitung based on Local Wisdom as a basic method for being able to read, write and count. 3) Implementing Script Schools in the form of training for tri blind housewives so as to improve the quality of life and income of the community.